Empowering Regional Tourism Stakeholders through Cooperative Learning: A Case Study Approach - MUSTAKIM; EMIRATI; MUTMAINNAH; JABRI, Umiyati; ARIANI, Nina (Politeknik Negeri Ujung Pandang, 2025)
Tourism holds great potential for regional development, particularly in culturally rich but underdeveloped areas like Enrekang Regency, South Sulawesi, Indonesia. However, limited human capital and fragmented stakeholder collaboration often hinder growth. This study explores the integration of the Cooperative Learning (CL) model into tourism education to enhance student competencies and support community-based tourism (CBT) development. Using a qualitative case study approach, data were collected through classroom observations, focus group discussions, and interviews with educators, students, tourism practitioners, and government officials. The findings reveal that CL significantly increased student engagement, strengthened English communication, leadership, and teamwork skills, and empowered students to lead real-world projects. These included the creation of 12 local tour packages, 7 digital promotional videos used by tourism offices, and the coordination of 5 village tourism events, contributing to increased local tourism visibility. Institutional support and cross-sector collaboration emerged as key success factors. The study concludes that embedding CL in tourism education not only enhances academic outcomes but also creates meaningful contributions to local tourism development. The model presented offers a replicable framework for aligning education with regional development goals, particularly in rural areas where tourism potential remains untapped